A broadband integrated microwave photonic mixer based on balanced photodetection - Zhenzhu Xu; Li Mei; Yuhua Chong; Xudong Gao; Shoubao Han; Chengkun Yang; Lin Li (Frontiers of Optoelectronics, 2023)
Abstract An integrated microwave photonic mixer based on silicon photonic platforms is proposed, which consist of a dual-drive Mach–Zehnder modulator and a balanced photodetector. The modulated optical signals from microwave photonic links can be directly demodulated and down-converted to intermediate frequency (IF) signals by the photonic mixer. The converted signal is obtained by conducting off-chip subtraction of the outputs from the balanced photodetector, and subsequent filtering of the high frequency items by an electrical low-pass filter. Benefiting from balanced detection, the conversion gain of the IF signal is improved by 6 dB, and radio frequency leakage and common-mode noise are suppressed significantly. System-level simulations show that the frequency mixing system has a spurious-free dynamic range of 89 dB·Hz2/3, even with deteriorated linearity caused by the two cascaded modulators. The spur suppression ratio of the photonic mixer remains higher than 40 dB when the IF varies from 0.5 to 4 GHz. The electrical-electrical 3 dB bandwidth of frequency conversion is 11 GHz. The integrated frequency mixing approach is quite simple, requiring no extra optical filters or electrical 90° hybrid coupler, which makes the system more stable and with broader bandwidth so that it can meet the potential demand in practical applications. Graphical Abstract